Carbamazepine-Induced Diarrhea - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Intractable diarrhea induced by carbamazepine (CBZ) in 3 patients and necessitating discontinuation of the drug is reported from the Departments of Neurology and Medicine, University of Louisville School of Medicine, Kentucky.